Factors Affecting Older Adult Adjustment at A Health Promoting Hospital in Nakhon Phanom, Thailand - Onuma Kaewkerd; Yuttachai Chaiyasit; Phensiri Dumrongpakapakorn; Nuttiya Prommasaka Na Sakonnakhon (Jurnal Keperawatan Indonesia, 2026)
Elderly adjustment influences quality of life and well-being and informs appropriate health promotion, holistic care, and health services. This study aimed to investigate the factors influencing the adaptation of older adults by focusing on a study conducted at Dong Kwang Health Promoting Hospital in Nakhon Phanom Province, Thailand. A cross-sectional design was used for the study. The sample consisted of 100 older adults and were selected for data collection from March 22, 2023, to April 20, 2023. The research instruments consisted of questionnaires assessing personal information, spiritual well-being, stress, perceived self-care abilities of older adults, quality of life, and older adult adjustment. The results indicated that the majority of the participants exhibited moderate levels of adjustment, with a mean score of 63.40 (SD = 8.99). A statistically significant correlation was found between stress and adjustment among older adults (r = .381, p = .001). Moreover, stress accounted for 11.00% of the variance in adjustment (p = .001). Nurses are recommended to reduce stress among older adults to enhance their adaptive capacity. Stress reduction interventions for older adults should be prioritized as they can enhance adaptive capacity and improve adjustment and quality of life in early old age.